2022
DOI: 10.1038/s41598-021-04309-1
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive analysis of selected medicines collected from private drug outlets of Dhaka city, Bangladesh in a simple random survey

Abstract: Comprehensive data are needed to prevent substandard and falsified (SF) medicines as they pose a major risk to human health. To assess the quality of selected medicines, samples were collected from random private drug outlets of Dhaka North and South City Corporation, Bangladesh. Sample analysis included visual observation of the packaging, authenticity of the samples, legitimacy and registration verification of the manufacturer, physicochemical analysis, and price. Chemical analysis of the samples was perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…30,31 However, it was close to that of Sch€ afermann et al (10%) for ciprofloxacin and metronidazole exclusively in a study conducted in Cameroon and DRC. 32 It was also approaching those found by Petersen et al 33 (7.1%) in Cameroon, Rahman et al 34 in Bangladesh (9.5%) and to the WHO global prevalence for the class of antibiotics and other antiinfective medicines (7.2%). 5 In fact, the problem could be more serious than it seemed as the present study only included two antiinfective medicines, a single pharmaceutical form, and a single dosage in three cities in Cameroon.…”
Section: Prevalence Of Sf Medicines and Cause Of Noncompliancementioning
confidence: 50%
“…30,31 However, it was close to that of Sch€ afermann et al (10%) for ciprofloxacin and metronidazole exclusively in a study conducted in Cameroon and DRC. 32 It was also approaching those found by Petersen et al 33 (7.1%) in Cameroon, Rahman et al 34 in Bangladesh (9.5%) and to the WHO global prevalence for the class of antibiotics and other antiinfective medicines (7.2%). 5 In fact, the problem could be more serious than it seemed as the present study only included two antiinfective medicines, a single pharmaceutical form, and a single dosage in three cities in Cameroon.…”
Section: Prevalence Of Sf Medicines and Cause Of Noncompliancementioning
confidence: 50%
“…Similar percentages of falsified medicines as in the present study have been reported in previous studies in LMICs, carrying out compendial analysis for all samples. e.g., Rahman et al 47 found 1.1% falsified samples in Bangladesh, and Hauk et al 31 found 1.7% in Cameroon and the DR Congo. No falsified medicines were found by Seitzer et al 48 among 88 samples from Burkina Faso, Cote d’Ivoire, Ghana and Tanzania.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the effective management of hypertension can impose significant financial strain on patients, potentially leading to dire consequences if the quality of the prescribed medications is compromised ( Al-Makki et al, 2022 ). Maintaining the quality of medications consistently poses a challenge for all involved stakeholders, including drug regulatory authorities, manufacturers, and patients on a global scale ( Pharmaceuticals & Medical Devices Bureau of India, 2023 , Rahman et al, 2022 , Kingori et al, 2019 , Newton et al, 2010 ). Manufacturers diligently strive to adhere to the standards set by regulatory authorities, aiming to ensure the optimal quality of their pharmaceutical products.…”
Section: Discussionmentioning
confidence: 99%